Respons Siswa SMK terhadap Media Pembelajaran Berbantuan Software MIT App Inventor 2 pada Materi Logika Matematika - Nafida Hetty Marhaeni; Melvinasari Melvinasari; Ika Amirin (Journal on Education, 2023)
This study aims to design and develop learning media based on android with software in mathematical logic material that is feasible for use by students. In this research, there are two stages that are carried out, that is designing learning application with MIT AI2 and do application usability testing. In the first stage, researcher design learning media on mathematical logic material for eleventh grade classes of vocational high school with use MIT AI2. Then, in the second stages testing the use of the application to determine its quality. In this research there were 13 participants to try to run the application then proceed to fill out the application usability questionnaire. The participants is students of the eleventh grade classes of SMK Muhhamadiyah 3 Wates. For instrument used are application made with MIT AI2 and student responses to the usability questionnaire. Questionnaire used to measure whether the application model can be well received by students according to application expectations or not. The results of the study show that researcher have succeeded in making learning media based android product with MIT AI2 that are feasible to be used by students with an average students response questionnaire of 90 and in good criteria.